CALCRETE FEATURES AND AGE ESTIMATES FROM U/TH DATING: IMPLICATIONS FOR THE ANALYSIS OF QUATERNARY EROSION RATES IN THE NORTHERN LIMB OF THE SIERRA NEVADA RANGE (BETIC CORDILLERA, SOUTHEAST SPAIN) - Azañón J.M.; Azor A.; Pérez-Peña J.V.; Tuccimei P.; Soligo M.; Sánchez-Almazo I.M.; Alonso-Zarza A.M. (My University, 2006)
The Guadix topographic depression is a Neogene-Quaternary basin located in the central sector of the Betic Cordillera at the boundary between the South Iberian margin and the Alboran domain. This topographic depression is a plateau with an average elevation of 1000 m in the northern limb of the Sierra Nevada range. The continental deposits infilling the Guadix basin span time from the late Tortonian to the Pleistocene, when a laminar calcrete developed on fine- to coarse-grained fluvial and lacustrine deposits. The drainage pattern is strongly incised (up to 200 m) below the calcrete layer. Four coeval subsamples from the top laminae of the calcrete were collected and dated by the U/Th method. The resulting date is 42.6 ± 5.6 ka, which indicates the minimum age for the cessation of active sedimentation in the Guadix basin. Using this age, we have calculated the incision and erosion rates for the late Pleistocene to present-day time span in the Arroyo de Gor, a highly incised canyon in the eastern border of the Guadix basin. The minimum incision rates in this canyon are around 4 mm/yr. We envisage the capture of the Pliocene-Pleistocene endorheic Guadix basin by the Guadalquivir River after 42 ka as the main factor triggering the formation of the present-day eroded landscape. After the capture, the combination of climatic (wet periods), lithological (soft and loose sediments), and topographic (high average altitude) features allowed the development of the present-day entrenched drainage pattern. © 2006 Geological Society of America.
Keywords: BETIC CORDILLERA; CALCRETES; GUADIX BASIN; QUATERNARY INCISION RATES; RIVER CAPTURE; SE SPAIN; STABLE ISOTOPES; U/TH DATING; Pleistocene; Pliocene; Tortonian; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен; Cenozoic::Neogene::Miocene::Tortonian; Кайнозой::Неоген::Миоцен::Тортонский